LAMINOPLASTY FUSION FOR CERVICAL SPINAL CORD INJURY WITH OSSIFICATION OF POSTERIOR LONGITUDINAL LIGAMENT: Combination technique for better result (Case Series) - Mahadewa, T. G. B. (BALI MEDICAL JOURNAL; Vol 4 No 3 (2015), 2015)
Background: This was a retrospective study of 10 cervical spinal cord injury (CSCI), concomitant with ossification of posterior longitudinal ligament (OPLL), that were treated by the author at Sanglah General Hospital-Bali during 2013-2014. The purpose of this study was to evaluate the efficacy of combination technique of laminoplasty with lateral mass screw fusion for canal compression due to OPLL in CSCI. There were 9 male patients of 10, average age was 58,3 years old. American Spinal Cord Injury Association (ASIA) scale preoperative was average in C scale and ASIA scale postoperative was in D. Mean JOA score preoperative was 9,5 and mean Japan orthopedic association (JOA) score postoperative was 13,3. Improvement after surgery using improvement formula of JOA was achieved by mean of 19,16%. All patients survived and improved neurologically, there was no surgical complication and implant failure in this series. No kyphotic deformity was observed in follow up cervical spine x-ray after 6 months. The author present a combination technique of 10 consecutive patients who underwent laminoplasty fusion for OPLL in CSCI with better result.
Keywords: cervical; spinal; cord; complication; kyphotic.